PLAC8 localizes to the inner plasma membrane of pancreatic cancer cells and regulates cell growth and disease progression through critical cell-cycle regulatory pathways - Kaistha, Brajesh Pratap; Lorenz, Holger; Schmidt, Harald; Sipos, Bence; Pawlak, Michael; Gierke, Berthold; Kreider, Ramona; Lankat-Buttgereit, Brigitte; Sauer, Melanie; Fiedler, Lisa; Krattenmacher, Anja; Geisel, Bettina; et al. (Cancer research, 2016)
Pancreatic ductal adenocarcinoma (PDAC) carries the most dismal prognosis of all solid tumors and is generally strongly resistant to currently available chemo- and/or radiotherapy regimens, including targeted molecular therapies. Therefore, unraveling the molecular mechanisms underlying the aggressive behavior of pancreatic cancer is a necessary prerequisite for the development of novel therapeutic approaches. We previously identified the protein placenta-specific 8 (PLAC8, onzin) in a genome-wide search for target genes associated with pancreatic tumor progression and demonstrated that PLAC8 is strongly ectopically expressed in advanced preneoplastic lesions and invasive human PDAC. However, the molecular function of PLAC8 remained unclear, and accumulating evidence suggested its role is highly dependent on cellular and physiologic context. Here, we demonstrate that in contrast to other cellular systems, PLAC8 protein localizes to the inner face of the plasma membrane in pancreatic cancer cells, where it interacts with specific membranous structures in a temporally and spatially stable manner. Inhibition of PLAC8 expression strongly inhibited pancreatic cancer cell growth by attenuating cell-cycle progression, which was associated with transcriptional and/or posttranslational modification of the central cell-cycle regulators CDKN1A, retinoblastoma protein, and cyclin D1 (CCND1), but did not impact autophagy. Moreover, Plac8 deficiency significantly inhibited tumor formation in genetically engineered mouse models of pancreatic cancer. Together, our findings establish PLAC8 as a central mediator of tumor progression in PDAC and as a promising candidate gene for diagnostic and therapeutic targeting. Cancer Res; 76(1); 96-107. ©2015 AACR.